A Story of Victimhood and Sacrifice? Self-Interpretation of the Fate of the Nation in Hungary and Belgium - Csorba, László; Verschaffel, Tom (Historical Studies on Central Europe, 2025)
Both in nineteenth-century Hungary and in Belgium, historians legitimizing the nation implied the people’s lack of freedom and suffering as a main theme in their narratives. The ‘myth of foreign occupations’ is crucial in their national narrative, as it was developed starting from the late eighteenth century, and with greater strength after the establishment of Belgium as an independent state in 1830. This implies that since the submission by the Romans in the first century BC, the Belgians had always been dominated by ‘foreign’ dynasties until they finally obtained freedom with the Belgian Revolution and independence. This is a romantic reinterpretation of the past and a myth, as in their own time the dynasties were considered legitimate, and not seen as ‘foreign.’ The national story of the “eighteen centuries of suffering and struggling” (as the popular Flemish novelist Henri Conscience phrased it) emphasizes the love of freedom and the courageous resistance to suppression by Belgians and their heroes. At the same time though the idea of the people’s victimhood and martyrdom, sometimes with a religious connotation, was an important motive in the national historical culture. The religious element is even stronger in the work of nineteenth-century Hungarian romantic thinkers. In fact, they reformulated an older way of thinking: When in 1526 the medieval Hungarian Kingdom collapsed and was divided into three parts, contemporaries tried to understand and explain this tragedy in biblical terms. The Bible teaches that people’s sins cause historical failures, but there is always hope because the sin and its punishment are proportional: Once we have suffered enough, the Almighty will help and support us if we deserve it. A pertinent example of the nineteenth-century rephrasing of this idea is the poem Himnusz [Hymn] by Ferenc Kölcsey, the official anthem of Hungary today. The motive faded in the second half of the century, due to the successes of modernization, but in the twentieth century, after the defeat of the dualistic monarchy in World War I, and under the weight of the severe pressure of the Trianon Peace Treaty, the mythology of victimhood was reborn. In Belgian historiography, it the idea of the ‘suppressed nation’ was taken over by the Flemish sub-nation, the Belgian state now presented by radical Flemish nationalists as a new (Francophone) oppressor.